Planning and installing solar thermal systems : a guide for installers, architects, and engineers (James & James/Earthscan, 2005)
Annotation * Adapted from the successful German edition, which has sold over 7,000 copies * Offers comprehensive guidance for professionals who wish to install solar thermal technology; in full color throughout * Includes details on how to market solar thermal technologies, a review of relevant simulation tools and data on selected regional, national and international renewable energy support programs Solar thermal systems available today offer efficiency and reliability. They can be applied in different conditions to meet space- and water-heating requirements in the residential, commercial and industrial building sectors. The potential for this technology and the associated environmental benefits are significant. This book offers clear guidance on planning and installing a solar thermal system, crucial to the successful uptake of this technology. Every subject necessary for successful project implementation is included. Beginning with resource assessment and an outline of core components, this guide details solar thermal system design, installation, operation and maintenance for single households, large systems, swimming pool heaters, solar air and solar cooling applications.
Keywords: Solar heating -- Installation.; Solar water heaters -- Installation.; Solar thermal energy.; elektronické knihy; electronic books